2022
DOI: 10.3390/medicina58070907
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Polysomnographic Features Associated with Poor Sleep Quality in Patients with Obstructive Sleep Apnea

Abstract: Background and Objectives: Poor sleep quality in patients with obstructive sleep apnea (OSA) may be associated with different clinical and polysomnographic features. The aim of this study was to identify features associated with poor sleep quality in OSA patients. Materials and Methods: This was a cross-sectional study enrolling patients with OSA confirmed by polysomnography (PSG). In addition to gathering clinical data, patients were assessed using the Pittsburgh Sleep Quality Index (PSQI), the Epworth Sleepi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…OSA patients showed significant increases in the ESS and the PSQI compared to the control group. These findings aligned with Kania et al [33], who found a strong relationship between sleepiness and sleep quality. Additionally, Buysse et al [34] confirmed that OSA was linked to sleep fragmentation caused by recurring arousal from apneas, resulting in excessive daytime sleepiness and inadequate sleep quality.…”
Section: Discussionsupporting
confidence: 92%
“…OSA patients showed significant increases in the ESS and the PSQI compared to the control group. These findings aligned with Kania et al [33], who found a strong relationship between sleepiness and sleep quality. Additionally, Buysse et al [34] confirmed that OSA was linked to sleep fragmentation caused by recurring arousal from apneas, resulting in excessive daytime sleepiness and inadequate sleep quality.…”
Section: Discussionsupporting
confidence: 92%
“…The comorbid relationship between sleep apnea and hypersomnia is high. While sleep apnea may be directly influencing hypersomnia, it is possible that other factors contributing to sleep apnea are also contributing to hypersomnia [55].…”
Section: Discussionmentioning
confidence: 99%
“…The cutoff for abnormal sleep is >5, and worse sleep quality is associated with higher scores [75]. The PSQI has been used in patients with OSA giving data on poor sleep quality related to cardiovascular comorbidities, daytime sleepiness, and nocturnal desaturation [76]. In a study including patients with COPD, PSQI scores were worse in patients with lower diffusion capacity [77], while higher scores correlated to exacerbation frequency [78] and increased symptoms according to CAT [79].…”
Section: Proms For the Evaluation Of Hrqol In Patients With Osmentioning
confidence: 99%
“…QoL impairment due to physical or emotional problems [49,50] 3 [49] Moderate-good correlations of all components to disease severity and symptoms (CAT) [59,60] Lower scores compared to general population [ ≥5 [75] Lower scores in patients with reduced DL CO [77] Higher scores correlated to exacerbation frequency [78] and increased symptoms (CAT) [79] Higher scores associated with CVD comorbidities, daytime sleepiness (ESS) and nocturnal desaturation [76] No difference in sleep quality compared to COPD only [80] SAQLI QoL in terms of daily functioning, social interaction, emotional functioning and symptoms [81] N/A Improvements in daily functioning component after high-intensity NIV therapy in stable hypercapnic COPD [83] Impaired QoL compared to controls [25]. Long-term improvements after CPAP treatment in severe and moderate OSA [82] N/A N/A for BDI (5 for BDI-II) [103] Associations with symptom severity [92], poor HRQoL [93] and exacerbation frequency [94] Increased levels of anxiety and depression compared to controls [91] N/A HADS Levels of anxiety and depression in a general medical population [95] 1.5 in COPD [104], 8 in OSA [96] Diagnostic of depression [98] Associations with disease severity [99] and exacerbation frequency [100].…”
Section: Sf-36mentioning
confidence: 99%